(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article, using the example of Uzbek folk tales, shows that the analysis of the lexical-semantic and linguocultural aspects of the language of folk tales, the worldview, ideas, attitude of proverbs to reality, their unique vision, perception, understanding and explanatory style, is of great importance.